Application of Virtual Assistant in Information System for Student Practicum Case Study Laboratory Informatics Department Siliwangi University - Cecep Muhamad Sidik Ramdani; Andi Nur Rachman; Euis Nur Fitriani Dewi (Universitas Negeri Medan, 2023)
Practical activities are carried out in an orderly and timely manner and require systematic recording of activities. The implementation of practicum activities takes place in the Siliwangi University laboratory, to create conducive conditions for practicum activities, a system must be able to support academic success. Not only that, due to the COVID-19 pandemic, previous practicum lectures were held offline and campus policy required online learning. These problems can be overcome by building a logbook information system that can record and keep records of laboratory activities automatically. This information system was created using the Extreme Programming system development method. Starting from database design, system design with UML, system development with Visual Studio. NET 2021. This technology can be used by universities for practical activities at the Siliwangi University Laboratory. The application will remind students to complete each activity in each session by displaying notifications in each practicum schedule, rewards, announcements, and other information related to practicum activities. All activities must be recorded in the application. Based on the results of black box testing, the system can run according to the system test design that the response from each student to the application used is 75.68% which can be concluded that the application of virtual assistant is in the interesting category.